A dream of justice : the story of Keyes v. Denver Public Schools - Pascoe, Pat (Timberline books., 2022)
"A Dream of justice is a firsthand account of the fight to desegregate Denver's public schools. Drawing on oral histories and interviews with members of the school board, legal community, parents, and students, as well as extensive institutional records, Pascoe offers a social history of Keyes v. Denver Public Schools"--